Travel Corridor Arrangement Application Process by Goverments of Indonesia and Singapore - Kurnianingsih, Fitri; Mahadiansar, Mahadiansar; Adhayanto, Oksep (Jurnal Bina Praja, 2022)
The discussion on the Travel Corridor Arrangement (TCA) between the Indonesian and Singaporean governments will continue in the future, but technically and practically, there are still certain issues that the Indonesian government has not addressed effectively. This demonstrates that we are technically still waiting for the correct judgement while the COVID-19 pandemic's case count declines. The goal of this article is to examine different research hypotheses on the elements that impact Indonesia's readiness for TCA with the Singapore government. The technique employed is a qualitative literature review. To bolster the literature review with secondary data, the researchers enhanced the examination of research hypotheses using the NVivo program, which was then thoroughly assessed. The findings indicate that researchers will also identify that Indonesia will be more sensitive to TCA than Singapore, resulting in the decision being rejected, while the next hypothesis is that TCA is also focused on tourists, as opposed to business activities between the two countries, and that the Indonesian government has also proposed implementing RGL, but RGL is not a priority, implying that TCA is more effective. if RGL is emphasized, the hypothesis may be accepted. This suggests that based on some of the results of these hypotheses, the rejection of the first hypothesis is due to a lack of expertise in Human Resource Management in implementing TCA with the Singapore government